Development of Toho Gas SOFC Cell Stack. (2nd June 2015) - Masuda, Soichiro; Ogura, Yusuke; Shimano, Jun
Abstract : Toho Gas has developed a planar type of scandia stabilized zirconia (ScSZ) electrolyte supported cell, and has been researching ways to improve performance of the cell stack. The present paper reports about a glass seal which is one of the major challenge in a planar type cell stack. The seal performance of two types of seals, paste and sheet, has been evaluated. As a result, it was indicated that the sheet seal improved the gas seal performance compared to the paste seal. Furthermore, the investigation for sheet seal contraction during seal forming process suggested that a load to seal should be controlled in order to define seal thickness after seal forming process.